FUNGSIONALISASI TEORI NASKH DALAM TAFSIR AL-QURâAN DAN HUKUM ISLAM: SEBUAH CATATAN KRITIS - Wardani, Wardani (Jurnal Ilmu Ushuluddin, 2014)
The commonly accepted assumption among Muslim scholars is that the abrogation (naskh)theory is regarded as method necessary for interpreting the Qurâan and for law-making. This articleis aimed to explore how it has been used and abused to support ideological interest. From thebeginning, some traditions, which are contradictory to each other, ascribed to âAlÃ® bin AbÃ® ThÃ¢lib,for instance, which supports the importance of knowledge on naskh, falls under unreliable category.The traditions have been distorted and interpreted in different context to argue for its importance.The naskh has been used to interpret some ambigous verses, such as what Ahmad Al-BahrÃ¢nÃ®, aShiite scholar, to set up his own theological beliefs. Meanwhile, the Muslim jurists have applied it asa method of making of law decision. âAbdullÃ¢h al-KarkhÃ® (w. 340 H), a Hanafite scholar, for instance,used it to attack against legal opinions of non-Hanafite scholars. Since al-ShÃ¢fiâÃ®âs era tillcontemporary time, the naskh has been regarded as a method of developing Islamic law, of course,in different contexts and trends.